Determining Gravity Wave Sources and Propagation in the Southern Hemisphere by Ray‐Tracing AIRS Measurements - Jon A. Perrett; Corwin J. Wright; Neil P. Hindley; Lars Hoffmann; Nicholas J. Mitchell; Peter Preusse; Cornelia Strube; Stephen D. Eckermann (Geophysical Research Letters)
Abstract Gravity waves (GWs) are key drivers of atmospheric circulation. Understanding their sources and propagation is essential to improving weather and climate models. We apply a 3D Stockwell Transform to 1 month of stratospheric temperature data from NASA's Atmospheric InfraRed Sounder to obtain 3D GW measurements and parameters. We use ray‐tracing methods to determine the sources and propagation characteristics of these GWs over the entire Southern Ocean. We trace 1.28 million GW measurements per day for the month of June 2010. Our analysis suggests that ground‐based sources around the Andes, Antarctic Peninsula, and Kerguelen play major roles, and that the GWs generated by these and other sources travel large zonal distances. We show evidence that GWs propagate into the 60°S belt, a possible source of “missing momentum flux” in GCMs at this latitude. These results emphasize the need for models to incorporate the possibility that GWs can exhibit large horizontal propagation.